Ethnomathematical Exploration of Geometric Concepts in Tegowangi Temple Ornaments - Bryant Candra Wijaya; Fanny Rahma Eka Aprianny; Amelia Putri Wahyuni; Jatmiko Jatmiko; Aprilia Dwi Handayani (Universitas Islam Tribakti Lirboyo Kediri, 2026)
This study explores geometric concepts embedded in the ornaments of Tegowangi Temple through an ethnomathematical perspective. Previous studies on temple-based ethnomathematics have primarily focused on general geometric forms, with limited attention to specific concepts and their pedagogical relevance, particularly in the context of Tegowangi Temple. Addressing this gap, this research aims to identify and analyse the concepts of reflection, similarity, and circles within the temple’s ornamental structures. A qualitative exploratory design with an ethnographic approach was employed. Data were collected through observation, interviews, and documentation, and analysed using domain and taxonomic analysis to interpret mathematical representations within cultural artefacts. The findings reveal that reflection is evident in the symmetrical structure of corner kala ornaments, in the similarity of the yoni's proportional dimensions, and in circular concepts in the decorative patterns of the Perwara Temple. These concepts were derived through systematic visual and structural analysis of ornament forms. Conceptually, the study contributes to a deeper understanding of geometry in cultural contexts, while pedagogically, it provides contextual learning resources for junior high school mathematics